2021
DOI: 10.1002/ange.202113266
|View full text |Cite
|
Sign up to set email alerts
|

Reactivities of Interstitial Hydrides in a Cu11 Template: En Route to Bimetallic Clusters

Abstract: In sharp contrast to surface hydrides,r eactivities of interstitial hydrides are difficult to explore.W hen treated with am etal ion (Cu + ,A g + ,a nd Au + ), the stable Cu I dihydride template [Cu 11 H 2 {S 2 P(O i Pr) 2 } 6 (C CPh) 3 ]( H 2 Cu 11 )g enerates surprisingly three very different compounds,n amely [CuH 2 Cu 11 {S 2 P(O i Pr) 2 } 6 (C CPh) 3 ] + (1), [AgH 2 Cu 14 {S 2 P-(O i Pr) 2 } 6 ((CCPh) 6 ] + (2), and [AuCu 11 {S 2 P(O i Pr) 2 } 6 (C CPh) 3 Cl] (3). Compounds 1 and 2 are both M I species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…Hence, the presence of the hydride is indisputable. Similarly, the same composition is observed for compound 2 compared to the previously published X-ray (denoted as 2b ) and neutron (denoted as 2b N ) structures . However, the three crystals were crystallized in different space groups ( 2 : C 2/ c , 2b : P 1̅, 2b N : P 2 1 / c ).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Hence, the presence of the hydride is indisputable. Similarly, the same composition is observed for compound 2 compared to the previously published X-ray (denoted as 2b ) and neutron (denoted as 2b N ) structures . However, the three crystals were crystallized in different space groups ( 2 : C 2/ c , 2b : P 1̅, 2b N : P 2 1 / c ).…”
Section: Resultssupporting
confidence: 80%
“…To supplement XRD analysis, computational methods such as Hirshfeld atomic refinement (HAR) have been developed, enabling anisotropic refinements for hydrogen atoms, although the accuracy is somewhat lower compared to atomic displacement parameters (ADPs) obtained from neutron diffraction. , It is important to consider the quality of the diffraction data, as insufficient data may limit the refinement to isotropic parameters. In contrast to theoretical calculations, a machine learning-based approach has also been employed to predict the possibility of hydride positions in copper hydride compounds. , The algorithm utilized in this method is trained with a limited data set of previously solved neutron crystal structures. One of the key benefits of employing machine learning in this context is its potential to accelerate the analysis process and decrease the reliance on costly and time-consuming experimental techniques. However, it should be emphasized that the accuracy and reliability of these methods are still undergoing assessment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[24][25][26] Specifically, in the catalytic regime, the strong electronic interaction between the alkynyl molecules and the metal can facilitate electron shuttling between the metal cores and the surface capping ligands, resulting in improved catalytic activity. [27][28][29][30][31][32][33][34] For instance, the Wang group documented that, for the semi-hydrogenation of alkynes, alkynyl-protected Au 38 nanoclusters exhibited nearly 100% conversion of a substrate with good product selectivity, but thiolate-protected Au 38 clusters demonstrated a negligible conversion rate. 5 In another study, the Tsukuda group reported a similar ligand effect in the electrochemical hydrogen evolution reaction (HER), where the onset potential of Au 25 (CuCR) 18 was about 70 mV more positive than that of Au 25 (SR) 18 under the same conditions.…”
Section: Introductionmentioning
confidence: 99%